STUDI KOMPARATIF STRATEGI INVESTASI GROWTH INVESTING DAN VALUE INVESTING DI PASAR MODAL INDONESIA - Na'afi, Septiana; Afrizal, Afrizal; Wijaya, Sean Michael Owen; Lukito, Laksono Edhi; Agustina, Wiwit (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze and compare the implementation of growth investing and value investing strategies in the Indonesian capital market. The research approach used is a qualitative comparative study method. Data were obtained through in-depth interviews with investors, capital market analysts, and academics, supported by literature and documentation in the form of issuer financial reports and publications from the Indonesia Stock Exchange. Informant selection was conducted using purposive sampling, while data analysis used the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results show that both growth investing and value investing are applied in the Indonesian capital market with various adjustments to the volatile market characteristics dominated by retail investors. Growth investing focuses more on a company's future growth potential and offers the opportunity for high returns, but is accompanied by significant volatility risks. Meanwhile, value investing emphasizes finding stocks that promise to be below their intrinsic value with a relatively lower level of risk, although requiring a longer investment period. This study also found that no investment strategy is absolutely superior, as the effectiveness of each strategy is strongly influenced by market conditions, investor characteristics, and investment objectives and horizons. This study concludes that understanding the characteristics of the Indonesian capital market and implementing investment strategies are crucial factors for investors in optimizing portfolio performance. These findings are expected to contribute theoretically to the study of investment strategies and serve as a practical reference for capital market investors in Indonesia.